A Diagnostic Evaluation of Etiology of Pancytopenia at a Tertiary Care Hospital - NAUMAN ASLAM MALIK, ROZINA JAFFAR, NIGHAT NASEEM, KALIM UD DIN MALIK, (Journal of Fatima Jinnah Medical University, 2018)
Objective: The objective of the study is to evaluate the etiology of pancytopenia in indoor and outdoor patients at LGH/PGMI Lahore. Study Design: A cross-sectional prospective observational study. Setting: Bone marrow clinic at LGH and PGMI Lahore. Duration: Jan 2008 – Dec 2011. A 4-year study conducted from Jan 2008 – Dec 2011.404 patients with pancytopenia were observed. Methodology: Complete blood counts, bone marrow aspiration and trephine biopsy were performed according to standard methods. Patients on cancer chemotherapy and radiotherapy were excluded. Results: Diseases leading to pancytopenia in the study in descending order of frequency were double deficiency anemia(iron deficiency anemia and megaloblastic anemia) 88 (25.6%), megaloblastic anemia 74 (21.5%), leukemia/lymphoma 66 (19.2%) and aplastic anemia 52 (15.1%). The less common causes include hypersplenism, 24 (7.0%), immune thrombocytopenic purpura 20 (5.8%), myclodysplastic/mycloproliferative disorders 10 (2.9%), storage disorders 6 (1.7%) and metastatic tumors 4 (1.2%). Conclusion: Double deficiency anemia (iron deficiency anemia and megaloblastic anemia), megaloblastic anemia, leukemia/lymphoma and aplastic anemia were the common causes of aplastic anemia.